Analisis Discover YIA (Airport Educated Tour) terhadap Kepuasan Pengunjung di Bandara Yogyakarta Internasional Airport - Nia Fitriya Dewi; You She Melly Anne Darasta (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Yogyakarta International Airport launched a new program, namely Discover YIA. Discover YIA is the first airport educational tourism program in Indonesia, therefore a visitor behavior survey is needed to determine visitor responses to the quality of services provided. The purpose of the study was to identify services and analyze the level of visitor satisfaction with the Discover YIA program at Yogyakarta International Airport. This study used quantitative methods. Quantitative methods are research that intersects with statistical data, therefore quantitative research can be generalized (Sugiyono, 2017). The results of testing the HO hypothesis are rejected and HA are accepted, there is a significant influence between the Discover YIA program variables on visitor satisfaction at Yogyakarta International Airport . The results of the simple linear regression test were 0.673 and the significant probability value was 0.000 0.05. The magnitude of the influence of the Discover YIA program on visitor satisfaction at Yogyakarta International Airport is 64.3%. It is recommended for the Discover YIA program to pay attention to and improve the quality of visitor services, based on this research, it shows that providing satisfactory service greatly influences visitor satisfaction of the Discover YIA program at Yogyakarta International Airport. Further researchers are advised to add insight and develop further research as a means of information for further research. This is so that it can be used as a comparison for this research. Kata kunci: Discover, Satisfaction, YIA